Manggaleh Culture-Based Experiential Learning in Social Entrepreneurship Education: A Preliminary Study in Social Studies Education - Cicilia Melinda; Bunyamin Maftuh; Kokom Komalasari; Acep Supriadi; Wisal Jereis Asad Alrabadi (Journal of Innovation in Educational and Cultural Research, 2026)
This study examines entrepreneurship education in the social studies education program, highlighting the limited integration of original socio-artistic surrounds in current practice. Approaches remain generally theoretical and techno-economic, leading to the underdevelopment of socio-entrepreneurial chops, particularly in social creativity and real-world problem solving. This study aims to dissect current literacy conditions and assess West Sumatra. A mixed-methods primary design was employed, involving compliance, semi-structured interviews, document analysis, and a questionnaire administered to lecturers and students from two universities. Data were analyzed using descriptive, qualitative, and quantitative approaches. The findings reveal a gap between lecturers' social exposure and students' profitable exposure, alongside dominant practices with minimal artistic integration. Although overall socio-entrepreneurial chops were fairly high (M=4.19), skills were linked to social perceptivity and invention (M=3.68). This study offers a culturally predicated Experiential learning frame grounded in Manggaleh values, furnishing a contextually applicable approach to bridging proposition and practice in socioentrepreneurship education.